Pengembangan Karir terhadap Intensi Turnover pada Tenaga Keperawatan - Resty, Dian Eka; Hariyati, Rr. Tutik Sri; Afriani, Tuti; Gayatri, Dewi (Journal of Telenursing (JOTING), 2024)
This study aims to evaluate the effect of career development on turnover intention in nurses. The research method used systematic review through electronic databases (ProQuest, Sage Journal, Science Direct). The results of 10 articles showed that positive career development, such as training and promotion opportunities, was associated with decreased turnover intention in nurses. Job satisfaction emerged as an important mediator in this relationship. In conclusion, effective career development can be an important strategy to reduce turnover intention in nurses. Hospitals need to invest in comprehensive and sustainable career development programs to improve job satisfaction and nurse retention. Further research is needed to explore the effectiveness of career development in reducing turnover intention in nurses, both through qualitative and longitudinal studies. Keywords: Turnover intention, Job satisfaction, Career development, Nurse retention